Perceptions of supervisors, teachers, and students regarding the new agricultural science syllabus for the Malaysian upper secondary schools - Nazri, Mohd Ibrahim (Universiti Putra Malaysia Press, 2006)
The Ministry of Education, Malaysia has reformed the school curriculum in accordance with the aspirations of the general public and economic development of the country. The new curriculum for secondary schools was introduced in stages beginning in 1989. The agricultural science subject had its new syllabus starting from 1993. The new syllabus was supposed to be more technological and integrative as compared to the old one. The purpose of the study was to obtain feedback from supervisors, teachers and students regarding the teaching of agricultural science subject based on the new syllabus. Specifically, the study sought the perceptions of respondents with regard to various aspects of agricultural science teaching in upper secondary schools. The research was a descriptive survey, employing a mailed questionnaire as the research instrument. The study included all teachers and supervisors of agricultural science. On the other hand, student respondents were purposively sampled. The instrument was pretested, yielding a reliability coefficient of .80. A total of 511 (61 %) usable questionnaires were received and analyzed. The response rate was 194 (57.4%) from teachers, 85 (63.9%) from supervisors, and 232 (58%) from students. The results revealed that all respondents were in agreement in term of their perceptions of the agricultural science project. However, the respondents were in less agreement.in their perceptions of the accomplishment of objectives, subject content, subject performance, implementation, students and evaluation. The study also revealed significant differences and associations between selected background variables of respondents with their perceptions. The research contributes significantly in providing insights regarding the present status of the agricultural science subject at upper secondary schools. The research findings are also useful as a basis for furthering development of the agricultural science subject.